The villa - Hawkins, Rachel, 1979- (New York : St. Martin's Press, 2023)
While on a girls trip to Italy with her best friend, Chess, Emily discovers their high-end villa was once the scene of a brutal murder, and, digging into the past, finds the truth seeping into the present as dangerous betrayals emerge.
"A novel" -- Cover.
Keywords: Brothers and sisters -- Fiction; Female friendship -- Fiction; Murder -- Fiction; Historical fiction; Thrillers (Fiction); Gothic fiction; Italy -- Fiction